Penguatan Literasi Biaya Produksi dan Harga Jual bagi Pengolah Hasil Laut Masyarakat Pesisir Kota Bengkulu - Muhammad Adnan Effendi Putra; Deasy Emalia (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aimed to improve the ability of coastal seafood processors in Bengkulu City to identify production costs and set selling prices more carefully. The activity was conducted using a participatory education approach through initial observation, short interviews, pre-test, practical training, worksheet-based simulation, mentoring, and post-test. The participants were 25 local seafood processors who produced dried fish, fish crackers, fish floss, and other simple processed products. The results showed that most participants previously set prices by following market habits or rough estimates without including labor, packaging, fuel, shrinkage, transportation, and equipment costs. After the training, the average understanding score increased from 52 to 82. Most participants were also able to prepare a simple production cost card and calculate selling prices using a cost-plus pricing approach. The activity concluded that practical and locally contextualized accounting education can help coastal microbusinesses avoid underpricing, understand their real profit, and become more confident in managing small household-based businesses.